Association between per- and polyfluoroalkyl substances and unexplained recurrent spontaneous abortion: A case-control study in China - Qianxi Cheng; Chunxian Lv; Yawei Li; Haocan Song; Shuyao Li; Dandan Li; Yingying Han; Feng Zhao; Qiang Lin (Ecotoxicology and Environmental Safety)
Although prior studies have identified that per- and polyfluoroalkyl substances (PFASs) were associated with adverse pregnancy outcomes, the potential influence of PFASs exposure on unexplained recurrent spontaneous abortion (URSA) remains uncertain. Our case-control study aimed to explore the associations between PFASs and URSA, including 110 URSA cases and 91 controls from Beijing. Concentrations of 15 PFASs in serum were measured using ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). The associations between PFASs and the risk of URSA were then analyzed using multiple logistic regression. Compared to the lowest tertile, PFBA (2nd (OR: 4.26; 95 % CI: 1.92, 9.45), 3rd (OR: 8.10; 95 % CI: 3.48, 18.89)), PFDoDA (2nd (OR: 2.17; 95 % CI: 1.72, 4.35), 3rd (OR: 3.18; 95 % CI: 2.24, 4.85)), PFHxS (3rd (OR: 2.46; 95 % CI: 1.15, 5.25) and PFHpS (3rd (OR: 2.56; 95 % CI: 1.15, 5.69) were positively associated with higher risks of URSA. 6:2 Cl-PFESA was significantly associated with decreased risks of URSA. Weighted quantile sum (WQS) regression analyses, Quantile g-computation (QGC) and Bayesian kernel machine regression (BKMR) identified PFBA and PFDoDA as the primary contributors to the mixed effects of PFASs on URSA. We found that maternal serum PFASs, especially PFBA and PFDoDA may increase the risk of URSA.